The Effect of Counseling on Dairy Milk Management on The Knowledge and Attitudes of Working Mothers - Rizkia Amilia; Nurul Qamariah Rista Andaruni; Cahaya Indah Lestari; Indriyani Makmun (Jurnal Kebidanan, 2022)
Based on data from the United Nations Children's Fund (UNICEF) in 2012, only 39% of babies under the age of 6 months receive exclusive breastfeeding worldwide. Riskesdas data in 2013 stated that the success of exclusive breastfeeding was only 54.3%. The coverage of exclusive breastfeeding can be increased if puerperal mothers, especially those who work, can apply dairy milk management. The purpose of this study is to analyze the effect of counseling on dairy breast milk management on the knowledge and attitudes of working mothers in the work area of the Karang Pule Health Center in Mataram City. This research is a pre-experimental design with a one-group pretest-posttest research design. The samples in this study were 30 samples with purposive sampling technique. The data were measured with questionnaires and analyzed using the Wilcoxon Match Pairs Test. The results of this study were that there was a difference in the average level of maternal knowledge of 2.48 and a difference in the average attitude of working mothers of breastfeeding of 24.29 with a p-value of 0.001 which means that there was a significant difference in the knowledge and attitudes of working mothers before and after being given counseling. The conclusion in this study is that there is an influence of counseling on the knowledge and attitudes of mothers working before and after being given counseling on dairy milk management. The suggestion from this study is expected to increase the knowledge and attitudes of working mothers about good dairy milk management so that it can be applied directly